NECESIDAD DE ESTABLECER UNA PENSIÓN ALIMENTICIA DIGNA PARA EL ADULTO MAYOR COMO GARANTÍA A SU DERECHO AL BUEN VIVIR - Feijoó Colambo, Leslye Michelle (2019)
The present thesis entitled: "Need to establish a decent alimony for the elderly as a guarantee of their right to well living" refers to the lack of resources that undermines the life of the elderly. Old age is the last stage of life, it is understood that upon reaching this stage the person has already made use of all his strength and abilities to fulfill his individual and collective obligations, therefore, his quality of life during old age should be favorable in the most possible and appropriate way to the needs that are presented. The provision of food is an obligation that is born in the family nucleus and the fulfillment of this depends a lot on the education that exists in the home, of the values and principles that put into practice the family members, strengthening the integral formation of the people. The rights of the elderly are determined and guaranteed in the Constitution of the Republic, at present, due to the lack of precision that regulates the different aspects of the right to food, the elderly is restricted from enjoying a dignified life and adequate to their conditions; Therefore, a project of legal reform the Civil Code must be elaborated, so that the elderly receive alimony from their descendants, taking into account family solidarity and co-responsibility as guiding principles that strengthen family relationships, but that is according to the real needs of the older adult, that is, knowing in advance their condition and the difficulties they face on a daily basis. In our country, the elderly are a vulnerable group, the protection and care of them must be proportional to the state or conditions that are found, and that every day is increasing and without any alternative solution by the State. Likewise, materials and methods were applied to develop this research and interviews and surveys were conducted, which have helped me to propose a legal reform project to the Childhood and Adolescence Code, so that senior citizens receive an alimony from their descendants and according to their needs